SUNFLOW ER-SUMMER LEGUMES INTERCROPPING SYSTEMS UNDER RAINFED CONDITIONS: ECONOMIC ANALYSIS - lbrar, Rashid; Ahmad, Shahbaz; Malik, M Azim (Biological Sciences - PJSIR, 2002)
Studies pertaining to the economic efficiency of intercropping summer legumes in sunflower under rainfed conditions were carried out at University of Arid Agriculture, Rawalpindi . Intercropping systems gave higher gross income, net income and benefit cost ratio than the sole cropping of component crops. Amongst the varoius intercropping systems studied, sunflower-mungbean combination proved to be the best as it gave the highest per hectare gross income (Rs. 18431.04), net income (Rs.10723.04) and benefit cost ratio (2.39) and it was followed by sunflower-soybean and sunflower-mashbean intercropping systems, respectively.